A multilayered cancer-on-a-chip model to analyze the effectiveness of new-generation photosensitizers. Issue 21 (27th August 2020) - Flont, Magdalena; Jastrzębska, Elżbieta; Brzózka, Zbigniew
Abstract : Three-dimensional (3D) cellular models of cancer tissue are necessary tools to analyze new anticancer drugs under in vitro conditions. Abstract : Three-dimensional (3D) cellular models of cancer tissue are necessary tools to analyze new anticancer drugs under in vitro conditions. Diagnostics and treatment of ovarian cancer are major challenges for current medicine. In our report we propose a new three-dimensional (3D) cellular model of ovarian cancer which can mimic a fragment of heterogeneous cancer tissue. We used Lab-on-a-chip technology to create a microfluidic system that allows cellular multilayer to be cultured. Cellular multilayer mimics the structure of two important elements of cancer tissue: flesh and stroma. For this reason, it has an advantage over other in vitro cellular models. We used human ovarian fibroblasts (HOF) and human ovarian cancer cells in our research (A2780). In the first stage of the study, we proved that the presence of non-malignant fibroblasts in co-culture with ovarian cancer cells stimulates the proliferation of cancer cells, which is important in the progression of ovarian cancer. In the next stage of the research, we tested the usefulness of the newly-developed cellular model in the analysis of anticancer drugs and therapies under in vitro conditions. We tested two photosensitizers (PS): free and nanoencapsulated meso -tetrafenylporphyrin, and we evaluated the potential of these drugs in anticancer photodynamic therapy (PDT) of ovarian cancer. We also studied the mechanism of PDT based on the analysis of the level of reactive oxygen species (ROS) in cell cultures. Our research confirmed that the use of new-generation PS can significantly increase the efficacy of PDT in the treatment of ovarian cancer. We also proved that the newly-developed 3D cellular model is suitable for rapid screening of anticancer drugs and has the potential to be used clinically in the future, e.g. in the selection of treatment methods for anticancer personalized medicine.